Identification of sensory dysfunction and nervous structure changes in Fam134b knockout mice. (2nd January 2023) - Chen, Binghao; Hu, Xingyun; Chen, Meiling; Chen, Yuying; Yan, Li; Zeng, Gang; Wang, Chuan; Liu, Lixuan; Yang, Chuan; Song, Weidong
ABSTRACT: Objectives: Mutation in human FAM134B gene has been implicated in hereditary sensory and autonomic neuropathy type IIB. We aimed to knock out Fam134b in mice and explored its phenotypes to determine whether the genetic impairments and behavioral changes can mirror manifestations noted in humans. Methods: We used CRISPR/Cas9 technology to knockout the Fam134b gene in the C57BL/6 J mouse. After confirming the knockout was successful by Sanger sequencing and Western blot, sensory function was measured using the hot plate test and the 50% paw withdrawal threshold test. In addition, standard microscopy and transmission electron microscopy were performed to observe the structural changes of the dorsal root ganglion sensory neuron and the sciatic nerve. Results: DNA sequencing and Western blot analysis confirmed the mutation in the Fam134b mutation gene and the loss of expression of its products. Fam134b knockout mice exhibited heat pain insensitivity and mechanical hyperalgesia. Interestingly, limb damage was found in some homozygotes. Demyelination in the sciatic nerve was common. Golgi bodies were turgid in dorsal root ganglion neuron. Conclusions: These findings indicate that peripheral neuropathy is common in Fam134b KO mice. We believe this novel animal model is likely to have significant future potential as a reliable model for the evaluation of peripheral neuropathy and its complications.